2014
DOI: 10.1111/are.12412
|View full text |Cite
|
Sign up to set email alerts
|

Growth compensation in juvenile tongue sole,Cynoglossus semilaevis(Güther, 1873): responses to thermal stress and feed restriction

Abstract: Responses of compensatory growth to high temperature and feed restriction in juvenile tongue sole, Cynoglossus semilaevis (G€ uther, 1873), were investigated during a 56-days experiment. Fish were divided into seven groups including three hightemperature treatments which were reared at 28°C for 1, 2 and 3 weeks, respectively, then returned to 22°C (recorded as T1, T2 and T3), three feedrestricted treatments which were fed 25% satiation for 1, 2 and 3 weeks, respectively, then fed ad libitum (recorded as R1, R2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Generally, the magnitude and duration of compensatory growth depend on the length of stress manipulation, that is severity of stress (Nikki et al., ; Qian et al., ; Tian & Qin, ). However, recovery period is also a key factor influencing the compensatory responses according to our previous research (Fang et al., ; Tian et al., ). The optimum temperature for the growth of hybrid grouper ranges from 26 to 30°C (De et al., ).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Generally, the magnitude and duration of compensatory growth depend on the length of stress manipulation, that is severity of stress (Nikki et al., ; Qian et al., ; Tian & Qin, ). However, recovery period is also a key factor influencing the compensatory responses according to our previous research (Fang et al., ; Tian et al., ). The optimum temperature for the growth of hybrid grouper ranges from 26 to 30°C (De et al., ).…”
Section: Discussionmentioning
confidence: 68%
“…Some previous studies have revealed that the body composition of fish that subjected to unfavourable conditions could be similar to that of the control after the compensatory growth (Fang et al., ; Heide et al., ; Tian et al., ). However, in the present study, after the 96‐day cyclical low‐temperature manipulation, the crude protein contents of fish in L2R14, L2R22, L4R12, L4R28 and L4R44 were significantly higher than those of control ( p < .05), suggesting that suitable repeating low‐temperature manipulation could be helpful to improve crude protein contents of fish.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation